Super-resolved fluorescence imaging utilising accessible stochastic optical reconstruction microscopy (easySTORM) implemented on a low-cost, modular open-source (openFrame) microscope - Bharadwaj,A; Kumar,A; Kalita,R; MITRA,R; Sharma,A; Jaganathan,BG; Bhattacharyya,J; Sarma,A; Garcia,E; Kumar,S; Lightley,J; Alexandrov,Y; et al. (Measurement Science and Technology, 2024)
Optical super-resolution microscope is a powerful tool for the life sciences, including cell biology and pathology yielding information on, e.g. biological structure and protein distribution in the nano-scale range. In recent years, there has been an exponential rise in the interest to apply super-resolution microscopes in diverse areas, but its wider utility is hindered by the cost of purchasing and maintaining super-resolved microscopes. In this paper we present the implementation of easySTORM, an accessible implementation of stochastic optical reconstruction microscopy (STORM) at Indian Institute of Technology Guwahati (IITG), India, in a flexible, user friendly and cost-effective manner using a state-of-the-art, modular, open-source, optical microscope platform called: 'openFrame'. Providing comparable imaging performance to commercial optical super-resolution microscopes, the openFrame-based implementation of easySTORM uses in-expensive multimode diode lasers and industry grade CMOS cameras, and the open-source and modular nature of the instrument makes it easy to maintain and to upgrade. To demonstrate its successful implementation at IITG, we image quantum dots and actin-tubulin structure in both normal and cancer cells, resolved features separated by a few tens of nanometers. This work demonstrates that openFrame-enabled easySTORM instrumentation can be widely accessible to provide affordable, research grade super-resolution microscopy capability for academic and medical research.